PEMAHAMAN NILAI – NILAI SYARIAH TERHADAP PERILAKU BISNIS PEDAGANG - Hardana, Ali (Institut Agama Islam Negeri Padngsidimpuan, 2016)
AbstractThis approach is conceptual which relied on Moslem law values and company identity literature. Besides research, empirical of its result is used to depict trap and opportunity use marketing communication means in strategy develop, build virtuous company brand. Result/conclusion A framework ethics which studying paradox relation link among/between is in perspective of consequences many supporter of marketing adopt behavior of merchant, and is in perspective of ethics which criticizing approach which orienting exclusive profit for the behavior of merchant. Herein after, Moslem law values strategy referring to marketing of behavior studied. To each, every that values strategy is exploration how company can avoid to fall into performance difference.Keyword: moslem law values, ethics of moralitas and behavior of merchant.